PUBLIC PARTICIPATION, WASTE MANAGEMENT, AND FLY CONTROL: IMPACT ON FLIES IN PANCUR BATU MARKET, DELI SERDANG - Tanjung, Dewi Rinanda; Nanda, Meutia; Purba, Faiqah Adnin; Suhaima, Maznil; Harahap, Rosida Sapriani (HEARTY, 2025)
Markets are vulnerable places for fly breeding, especially when waste management and fly control are not properly implemented. Therefore, active community participation is crucial in maintaining market cleanliness through proper waste management and effective fly control. This study aims to examine the influence of community participation in waste management and fly control on the presence of flies at Pancur Batu Market, Deli Serdang Regency, North Sumatra. The research used a quantitative method with a cross-sectional approach. The sample size in this study was 54 respondents, and the data were analyzed using univariate and bivariate analysis with the chi-square test. Based on the analysis results, there was a significant relationship between waste management and fly control with the level of fly presence at Pancur Batu Market (p < 0.05). Respondents with poor waste management and inadequate fly control had a higher risk of experiencing high fly presence. Poor waste management increased the risk by 2.246 times, while poor fly control increased the risk by 2.010 times compared to those with good management and control. These findings highlight the importance of community participation in optimizing waste management and fly control efforts to reduce fly populations in market environments.